2021
DOI: 10.3390/buildings11100448
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Architectural Designers’ Continuous Use Intention Regarding BIM Technology: A China Case

Abstract: Despite BIM technology influencing architectural design companies profoundly, there has still been an under-representation of architectural designers’ continuous use intention (CUI) regarding it. This paper aims to empirically examine what factors can potentially affect architectural designers’ CUI of BIM through the integration of a technology acceptance model (TAM) and an expectation confirmation theory (ECT). Sample data for empirical research were collected from architectural design companies in Qingdao, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…Non-parametric statistical tests were conducted to analyse the data from the questionnaire since the data were obtained on an ordinal measurement scale and had non-normal distribution [53]. CFA and SEM approach was implemented by the utilization of Analysis of Moment Structure (IBM SPSS AMOS, Version 26.0) software package, which is widely used in construction management studies [54,55]. The methods and statistical tests used in this study are briefly described below:…”
Section: Discussionmentioning
confidence: 99%
“…Non-parametric statistical tests were conducted to analyse the data from the questionnaire since the data were obtained on an ordinal measurement scale and had non-normal distribution [53]. CFA and SEM approach was implemented by the utilization of Analysis of Moment Structure (IBM SPSS AMOS, Version 26.0) software package, which is widely used in construction management studies [54,55]. The methods and statistical tests used in this study are briefly described below:…”
Section: Discussionmentioning
confidence: 99%
“…If the online streaming service is considered easy to use, then this service will also be considered useful. Finally, software development companies can be inspired by the results of this study to better consider software functionality from the perspective of ease of use and convenience (Qinghong Cui et al, 2021). The evaluation results in Table 4 show the path coefficient value of 0.173.…”
Section: Figure 2 Pls Algorithm Structural Modelmentioning
confidence: 97%
“…However, ease of use was found to have a positive and significant effect on perceived usefulness. Another study by Qinghong Cui et al (2021) regarding the intention to use BIM Technology found that ease of use positively influences users' perceived usefulness. According to Humbani & Wiese (2019), in their research on the adoption and repeated use of mobile payment applications, it is not proven that perceived usefulness have a positive effect on intentions to use mobile payment applications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the number of studies on BIM is increasing daily, it is noteworthy that the number of studies using this modelling method remains low. When the limited researches modelled the variable and examined BIM, it is evident that the studies focused on modelling the relationship between BIM attributes and environmental sustainability (Mirpanahi and Noorzai, 2021); collaborative innovation activities and BIM application (Qiao et al, 2021); impact of BIM drivers and awareness on the project lifecycle (Olanrewaju et al, 2021); risks associated with BIM implementation and adoption (Zhao et al, , 2018; work-based education and BIM adoption (Semaan et al, 2021); teamwork efficiency and BIM-based collaborative design (Wang et al, 2021); continuous use intention of BIM (Cui et al, 2021); factors hindering BIM implementation (Liao et al, 2019); factors predicting the behavioural resistance to BIM implementation (Wang et al, 2020); critical BIM adoption drivers across the infrastructure construction sector (Belay et al, 2021); the impact of organisation size and project type on BIM adoption (Hong et al, 2019); the BIM-related factors affecting the project performance (Tam et al, 2021); the strategies improving the organisational BIM capabilities (Munianday et al, 2022).…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…, 2021); teamwork efficiency and BIM-based collaborative design (Wang et al. , 2021); continuous use intention of BIM (Cui et al. , 2021); factors hindering BIM implementation (Liao et al.…”
Section: Research Background and Gaps In Literaturementioning
confidence: 99%